A Note on a Functional Differential Equation with State Dependent Argument (Communications in Mathematical Research, 2019)
This paper is concerned with solutions of a functional differential equation.Using Krasnoselskii's fixed point theorem, the solutions can be obtained fromperiodic solutions of a companion equation.